Dakwah dalam Masyarakat Multikultural di Indonesia - Ayu Windri; Elismayanti Rambe (PT. Willy Print Art, 2024)
Indonesia could be a nation which has so numerous ethnicities, tribes, societies, dialects, and religions. Such diversity is inclined to strife and friction and so, there must be a orderly, modified, coordinates, and economical exertion to preserve the keenness of the country and as a multicultural country.A step to be taken to realize it is by planting a multicultural understanding to the society. Planting a multicultural understanding isn't planning to kill contrasts but to kill inclination, create dialogs and get to know the contrasts among them, so that shared regard and appreciation can be achieved. One shape of planting a multicultural understanding can be a dakwah action which applies a social approach that's grounded in all inclusive values of humanity.